The Spanish version of the Level of Personality Functioning Scale – Brief Form 2.0 (LPFS-BF 2.0): Psychometric evaluation in adolescents who have suffered from parental abuse and neglect and a community sample - Balzen Kennedy M.; Sharp Carla; Unzurruzaga Erne; Eguren Ane; Pérez Luis (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology)
Given shifts to dimensional models of personality pathology and a growing consensus that personality disorder (PD) often onsets during adolescence, there is a need for validated measures of PD in adolescents. Level of Personality Functioning (LPF) is particularly relevant for the identification of emerging personality dysfunction in adolescents given its ability to capture developmental discontinuity as metacognitive capacities in self- and interpersonal-functioning emerge. However, no studies as of yet have validated a measure of LPF in a sample of Spanish-speaking adolescents. In addition, no study has evaluated whether LPF associates with status as victim of parental neglect vs. community adolescents. A total of 570 Spanish-speaking adolescents between the ages of 11 and 18 (n = 168 with a history of parental neglect, n = 402 from a community sample) completed the briefest form of LPF, the LPFS-BF 2.0. Results from the confirmatory factor analysis revealed adequate fit of a unidimensional model, and invariance analyses suggested measurement invariance across gender and age (early versus late adolescents). Internal consistency was adequate, and convergent validity was supported through negative correlations of the LPFS-BF 2.0 with empathy and reflective function, and positive associations with alexithymia. Contrary to expectations, total scores on the LPFS-BF 2.0 did not distinguish adolescents with a history of parental neglect and adolescents from a community sample. Overall, results support the Spanish translation of the LPFS-BF 2.0 as a valid measure for use in adolescents.